Analisis Hubungan Antara Omset Penjualan Pedagang Kue, Penggunaan Tepung Terigu Dan Jenis Kelamin Menggunakan Model Log Linier - Azwar Habibi (ESTIMASI: Journal of Statistics and Its Application, 2023)
The aim of the study was to determine the pattern of relationship between the sales turnover variables of cake vendors, the use of wheat flour, and gender. Knowing the best equation model that shows the relationship pattern of cake vendor sales turnover variables, the use of wheat flour, and gender. Determine the cells that cause the relationship between variables to be dependent. The data analysis method used in this research is the Linear Log Model with the best model using the Backward method. The data in this research is secondary data from a survey at PT. BOGASARI in November 2022. The conclusions obtained in this study are that there is a relationship between the variable sales turnover of traders every day and the use of wheat flour for golden carriages. The best model showing the pattern of relationship between the sales turnover variables of cake vendors, the use of carriage golden flour, and gender is log . Male traders whose daily turnover is < Rp. 500,000.00 tend to use Kereta Kencana flour, while female traders whose turnover is < Rp. 500,000.00 per day tend not to use Kereta Kencana flour.